Cell adhesion and spreading on fluid membranes through microtubules-dependent mechanotransduction - Oleg Mikhajlov; Ram M. Adar; Maria Tătulea-Codrean; Anne-Sophie Macé; John Manzi; Fanny Tabarin; Aude Battistella; Fahima di Federico; Jean-François Joanny; Guy Tran van Nhieu; Patricia Bassereau (Nature Communications)
Abstract Integrin clusters facilitate mechanical force transmission (mechanotransduction) and regulate biochemical signaling during cell adhesion. However, most studies have focused on rigid substrates. On fluid substrates like supported lipid bilayers (SLBs), integrin ligands are mobile, and adhesive complexes are traditionally thought unable to anchor for cell spreading. Here, we demonstrate that cells spread on SLBs coated with Invasin, a high-affinity integrin ligand. Unlike SLBs functionalized with RGD peptides, integrin clusters on Invasin-SLBs grow in size and complexity comparable to those on glass. While actomyosin contraction dominates adhesion maturation on stiff substrates, we find that on fluid SLBs, integrin mechanotransduction and cell spreading rely on dynein pulling forces along microtubules perpendicular to the membranes and microtubules pushing on adhesive complexes, respectively. These forces, potentially present on non-deformable surfaces, are revealed in fluid substrate systems. Supported by a theoretical model, our findings demonstrate a mechanical role for microtubules in integrin clustering.